Association of tirzepatide with changes in OSA-related measures based on baseline characteristics – post hoc analyses of SURMOUNT-OSA - Beverly Falcon; Cathy Chang Xie; Susan Redline; Ronald Grunstein; Christopher D. Turnbull; David M. Rapoport; Hui Wang; Sujatro Chakladar; Georgios K. Dimitriadis; Eva Lau; Jo Bednarik; Birong Liao; et al. (Journal of Clinical Sleep Medicine, 2026)
Abstract Purpose Obstructive sleep apnea (OSA) is a common disorder characterized by repetitive collapse of the upper airway during sleep. Given that excess adiposity is a known risk factor for OSA, we aimed to descriptively assess the association of tirzepatide, a GIP/GLP-1 receptor agonist, with changes in AHI, hypoxic burden, body weight, and blood pressure in different patient populations based on baseline characteristics such as age, sex, BMI, AHI, and neck circumference. Methods These post hoc analyses examined data from two Phase 3 randomized, double-blind studies evaluating maximum tolerated dose (MTD) tirzepatide (10 mg or 15 mg) compared with placebo in adults with moderate-to-severe OSA (AHI ≥ 15 events/h) and obesity (BMI ≥ 30 kg/m 2 ) over a 52-week period. Baseline subgroup analyses were conducted in participants with non-missing relevant baseline measurements. Results Generally, participants treated with tirzepatide showed greater improvements in OSA outcomes compared with placebo, regardless of baseline subgroup. Participants treated with tirzepatide experienced reductions in AHI across subgroups, regardless of baseline age (-27.7 to -34.1 events/h), sex (-19.8 to -32.6 events/h), AHI severity (-12.1 to -52.2 events/h), BMI (-25.2 to -34.4 events/h), and neck circumference (-23.9 to -30.8 events/h). Additionally, improvements were observed in body weight, systolic blood pressure, and sleep apnea-specific hypoxic burden across baseline subgroups. Overall, most participants experienced an improvement in AHI severity category with tirzepatide treatment (68% to 79%), while the majority in the placebo group saw no clinically relevant change (64% to 70%). Conclusions In these descriptive, hypothesis-generating, post hoc analyses, tirzepatide treatment was associated with improvements in multiple measures in participants with moderate-to-severe OSA and obesity. These improvements were observed across both studies, regardless of baseline age, sex, AHI severity, BMI, or neck circumference. Clinical Trial Registration SURMOUNT-OSA program (NCT05412004). Brief summary Current knowledge/study rationale Tirzepatide has been associated with clinically relevant improvements in OSA-related measures, body weight, and systolic blood pressure among individuals with moderate-to-severe OSA and obesity. These post hoc analyses aimed to assess whether there were variations in improvements based on baseline age, sex, AHI severity, BMI, or neck circumference. Study impact In general, tirzepatide treatment was associated with improvement in OSA outcomes across both studies, regardless of baseline age, sex, AHI severity, BMI, or neck circumference, with some observed differences among some baseline characteristics. This research may help us better understand the relationship between baseline characteristics and different OSA treatment responses and may stimulate future studies in this area.